2015
DOI: 10.2139/ssrn.2704253
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Extreme Weather Events on Education

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…It is above the average in this respect compared to other countries in the Central Asian region. Basic education is free and the government provides subsidized boarding schools for children from herder families (Groppo & Kraehnert, 2016) as boarding school dormitories have been the best practice for schooling of herders (Ahearn & Bumochir, 2016). Boarding schools make a valuable contribution toward encouraging herder families to send their children to school in the nation.…”
Section: The School Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…It is above the average in this respect compared to other countries in the Central Asian region. Basic education is free and the government provides subsidized boarding schools for children from herder families (Groppo & Kraehnert, 2016) as boarding school dormitories have been the best practice for schooling of herders (Ahearn & Bumochir, 2016). Boarding schools make a valuable contribution toward encouraging herder families to send their children to school in the nation.…”
Section: The School Systemmentioning
confidence: 99%
“…Recent statistics show that a full-time herder household owns an average of 323 head of livestock (NSOM, 2016). In the nomadic culture, herder families often move around for better pastures, and a recent study has found that most herders move their herds 2 to 25 times per year (Groppo & Kraehnert, 2016). Lkhagvadorj et al (2013) have reported that the livelihoods of herder households heavily rely on the income derived from livestock products.…”
Section: The Herder Familymentioning
confidence: 99%
See 3 more Smart Citations